Russian perspective of the Anglo Boer War (Historia, 2021)
The South African War centenary commemoration has given rise to a considerable industry involving mementoes, exhibitions, tourism, some historical revisionism (to reflect the new social realities of South Africa) and publications. The work under review strikes one as yet another attempt to tap into the reading market created by the centenary. Admittedly the perspective that the authors have taken, that of Russian involvement, appears to hold a lot of potential in reviving palates that have become somewhat jaded by seemingly unending servings of an increasingly boring dish.The prologue to the work provides some fleeting insight into the problems that confronted Davidson and Filatova in locating their sources and the all-pervasive influence of the Soviet system that persuaded participants in the war and their heirs to destroy their records in order to obscure their aristocratic origins or links with the imperial army and security services. It also offers some insight into the problems confronting the Soviet academic undertaking politically incorrect research.
Keywords: Davidson and Filatova; Soviet system; Anglo-Boer Wars; Russian Jews